Teachers Training For Making Online Learning Media During The Covid-19 Pandemic in SMAN 1 Rantau Utara - Rambe, Isnaini Halimah; Syahputra, M.R; Br Sembiring, Metrilitna; Octariani, Dhia; Mardiana, Nana; Matondang, Asnawati; Nila, Safina; `, Atmawarni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity program aims to improve the skills of teachers in making learning media during the pandemic at SMAN 1 Rantau Utara. The method used is descriptive method. The steps used are by providing socialization, lectures and assistance in the process of making learning media during the pandemic. The results of the response of the training participants gave a positive response. Participants gave suggestions in this activity to continue in self-development for teachers at SMAN Rantau Utara.